UNILATERAL TONSILLAR ENLARGEMENT – A CASE SERIES - SUMITHA .R; HAFIDA K MOHAMED (International Journal of Pharma and Bio Sciences, 2013)
Unilateral Tonsillar Enlargement is more common in adult age group and is increasingly seen in the Department of Ear, Nose & Throat. Frequently these patients are listed for tonsillectomy for the purpose of ruling out malignancy. Since most of the cases of Unilateral Tonsillar Enlargement are benign pathology, tonsillectomy for these patients was decided on the basis of risk factors avoiding unnecessary surgical intervention for all patients. We reviewed 108 patients who underwent tonsillectomies from 2011 to 2012 of which 7 (seven) cases were done due to asymmetry in tonsil. All the risk factors for malignancy like Cervical lymph node enlargement, Sex, Age, Tonsillar size were evaluated and out of 11(eleven) cases of Unilateral Tonsillar Enlargement during the study period 2011 – 2012, 7( seven) were taken up for surgery. Histo pathological evaluation showed 85.7% to be benign and 14.3% to be malignant. In our study, the alarming risk factor was cervical lymph node enlargement and alcohol consumption. Lymphomas are the commonest cause of Unilateral Tonsillar Enlargement but all Unilateral Tonsillar Enlargements are not lymphomas. Therefore strict evaluation of all risk factors is mandatory before exposing patients to surgeries like tonsillectomy.